Modernizing America’s Data Backbone: Integrating Cloud Lakes, Warehouses, MDM, and Analytics for National Resilience - Metla, Sasidhar (International Journal of Computing and Engineering, 2025)
Military commanders are making life-or-death decisions. Emergency responders are racing against time during disasters. American businesses are fighting for survival against global competitors. What connects these scenarios? Their success increasingly depends on how effectively they handle critical information. This article examines four breakthrough technologies that are changing everything about how organizations harness data. Cloud Data Lakes have completely transformed storage economics—breaking the traditional link between computing and storage costs. Organizations can now keep massive information collections without watching budgets explode. Meanwhile, Data Warehouses have evolved dramatically from glorified storage bins into analytical powerhouses. Systems that once made analysts wait hours for basic answers now deliver complex insights almost instantly. Master Data Management finally solves the maddening problem of conflicting information, such as when five different systems show five different customer addresses. By establishing single, authoritative records across critical domains, organizations eliminate endless reconciliation headaches. Perhaps most importantly, advanced analytics tools—once restricted to specialized departments-now help workers throughout organizations spot emerging patterns and predict what's coming next.